π-Acid Mediated Insertion of Alkynes into Carbon–Heteroatom σ-Bonds - Adcock, Holly V.; Davies, Paul W. (Synthesis, 2012)
The rapidly expanding field of gold and platinum π-acid catalysis has led to the discovery of diverse transformations that are initiated with nucleophilic attack onto a metal-activated alkyne. This review brings together those reactions which employ a heteroatom nucleophile bearing a functional group that can subsequently migrate to effect a formal insertion of the alkyne into a carbon–heteroatom σ-bond. This reactivity profile is encountered in a range of efficient and powerful cycloisomerisations for the preparation of carbo- and heterocycles.1 Introduction 2 1,2-Addition of Carbon–Heteroatom Bonds across Alkynes2.1 Heteroatom-to-Carbon Allyl Migrations2.2 Accessing Sigmatropic Rearrangements2.3 Related Palladium-Catalysed 1,2-Carboalkoxylations and Carboaminations2.4 Beyond Allyl Migration in the 1,2-Carbofunctionalisation of Alkynes2.5 Oxonium Ion Migration2.6 Migrating Centres at Higher Oxidation Levels2.7 Migration of Heteroatoms3 1,5 Heteroatom-to-Carbon Migrations3.1 Alkynyl Benzoates as Alkylating Agents4 Internal versus External Migrations4.1 Internal Migrations of Oxonium Species5 1,1-Carbofunctionalisations6 Application in Natural Products7 Summary and Conclusions
Keywords: catalysis; gold; platinum; alkynes; nucleophilic addition; cyclisation; heterocycles